2020
DOI: 10.1111/cei.13515
|View full text |Cite
|
Sign up to set email alerts
|

The rise of complement in ANCA-associated vasculitis: from marginal player to target of modern therapy

Abstract: The complement system plays a central role in autoimmune diseases, including anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Although complement deposition is scarce in AAV pathological samples, complement activation is required for the development of necrotizing crescentic glomerulonephritis (NCGN) in mouse models of AAV and occurs via the alternative pathway. The anaphylatoxin C5a, produced by the final complement pathway, is determinant to drive the disease in animal models. C5a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…It is pertinent to mention that almost all kidney diseases appear to a have strong complement component related to their pathophysiology, which is outside the scope of this review but might be a target for complement therapy. A kidney disease in which complement target therapy has advanced to a stage wherein we may anticipate that it will be incorporated into the treatment arsenal is accompanied by necrotizing crescentic glomerulonephritis ( Trivioli and Vaglio, 2020 ). This disease is discussed further under the systemic autoimmune chapter item 6 in the section below.…”
Section: Therapeutic Complement Inhibitionmentioning
confidence: 99%
“…It is pertinent to mention that almost all kidney diseases appear to a have strong complement component related to their pathophysiology, which is outside the scope of this review but might be a target for complement therapy. A kidney disease in which complement target therapy has advanced to a stage wherein we may anticipate that it will be incorporated into the treatment arsenal is accompanied by necrotizing crescentic glomerulonephritis ( Trivioli and Vaglio, 2020 ). This disease is discussed further under the systemic autoimmune chapter item 6 in the section below.…”
Section: Therapeutic Complement Inhibitionmentioning
confidence: 99%
“…In kidney biopsies from AAV patients, NETs comprising DNA, histones, granule proteins MPO, PR3, LL37, and NE were found in the glomeruli ( 20 ). In addition, levels of inflammatory mediators such as tumor necrosis factor-alpha (TNF-α) and C5a were increased in AAV patients and these can also promote the migration of intracellular MPO and PR3 from the cytoplasm to the cell membrane or into the extracellular space ( 21 , 22 ).…”
Section: Vasculitis: Immunopathogenesis and Alterations In Cellular Signaling Pathwaysmentioning
confidence: 99%
“…Further neutrophil priming occurs when C5a binds to the C5a receptor (C5aR), activating neutrophils and attracting more neutrophils to the inflammatory site, and the subsequent production of neutrophil extracellular traps (NETs). 12,13,[15][16][17] These interactions result in acute inflammation, with hyperactivation of neutrophils, increased cytokine production, a respiratory burst with the release of reactive oxygen species, degranulation of lytic enzymes, and the release of tissue factor-bearing microparticles and NETs. 12,16 NETs can induce endothelial damage due to their association with matrix metalloproteinases and may play important roles in the promotion of atherosclerosis and thrombosis.…”
Section: Pathophysiology Of Anca Vasculitismentioning
confidence: 99%
“…Of these, avacopan, an orally administered inhibitor of the complement C5a receptor, is the only agent that has been assessed in a phase 3 clinical trial. 17,51,52 Although limited to results from a small, open-label study, the selective costimulation modulator abatacept has shown promising results. 53 Belimumab, a monoclonal antibody directed against B-lymphocyte stimulator (BLyS), has been evaluated, thus far with equivocal results, in combination with azathioprine for the maintenance of remission in patients with GPA and MPA.…”
Section: Advances In the Treatment Of Anca Vasculitismentioning
confidence: 99%